2014
DOI: 10.1259/dmfr.20140016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic features of the adenomatoid odontogenic tumour on cone beam CT

Abstract: Objectives: To illustrate characteristic features of adenomatoid odontogenic tumour (AOT) on CBCT. Methods: The archived CBCT and panoramic radiographs of eight patients histopathologically diagnosed as AOT were analysed. The radiographic features displayed on both radiographic images were carefully described and compared. Results: All eight AOT cases presented as unilocular and well-demarcated lesions on both CBCT and panoramic images. CBCT images displayed three-dimensional interpretation of AOT lesions, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…A similar study performed by Jiang et al . [19] reported that CBCT was better than panoramic radiography in AOT diagnosis. They reported that only CBCT was able to detect thin and minimal calcifications.…”
Section: ⅱ Case Reportmentioning
confidence: 99%
“…A similar study performed by Jiang et al . [19] reported that CBCT was better than panoramic radiography in AOT diagnosis. They reported that only CBCT was able to detect thin and minimal calcifications.…”
Section: ⅱ Case Reportmentioning
confidence: 99%
“…Im Rahmen der Weichteildiagnostik sind die Sonografie zur Darstellung des Tumors und der umgebenden Strukturen und bei ausgedehnten Befunden oder vorliegendem Verdacht auf ein Malignom auch ein MRT mit Kontrastmittel in Erwägung zu ziehen (35). Bei fraglicher Beteiligung oder Infiltration knöcherner Strukturen kann neben konventionellen Methoden wie der Panoramaschichtaufnahme (PSA) in Einzelfällen auch die digitale Volumentomografie (DVT) oder eine CT erforderlich sein (11). Die große Befundvariabilität und daher schwierige klinische Differenzialdiagnostik erfordert zur Diagnosesicherung grundsätzlich eine feingewebliche Untersuchung gewonnener Gewebeproben nach erfolgter Inzisions-, Exzisions-oder Feinnadelstanzbiospie.…”
Section: Klinik Und Diagnostikunclassified
“…Images obtained using CBCT provide the clinician with great detail and much information, allowing the presence of previously undiagnosed pathoses 66,72 or absence of odontogenic aetiology of pain 73,74 to be verified. However, no single test or imaging technology will provide a definitive diagnosis.…”
Section: Evaluation Of Root Canal Anatomy and Complex Morphologymentioning
confidence: 99%